Angular momentum and energy-momentum densities as gauge currents - Calçada, M. [UNESP]; Pereira, J. G. [UNESP] (American Physical Society (APS), 2002)
If we replace the general spacetime group of diffeomorphisms by transformations taking place in the tangent space, general relativity can be interpreted as a gauge theory, and in particular as a gauge theory for the Lorentz group. In this context, it is shown that the angular momentum and the energy-momentum tensors of a general matter field can be obtained from the invariance of the corresponding action integral under transformations taking place, not in spacetime, but in the tangent space, in which case they can be considered as gauge currents. ©2002 The American Physical Society.